Highlights of Climate Smart Agriculture (CSA) Knowledge Hub in Ethiopia. Activity Report - Adimassu, Zenebe; Tibebe, Degefie; Kebede, Fikiru; Abera, Wuletawu; Tamene, Lulseged (2025)
The Climate-Smart Agriculture (CSA) Knowledge Hub was developed to meet the growing demand for accessible, centralized information on CSA practices in Ethiopia. CSA promotes sustainable agriculture by enhancing productivity, building resilience to climate change, and reducing greenhouse gas emissions. The Hub serves farmers, researchers, policymakers, and development practitioners by providing resources such as data, case studies, technologies, and policy guidance. Its key sections include a homepage, an "About Us" section outlining CSA concepts and the Hub’s purpose, an "Explore" section with a searchable CSA database categorized by publication type, outcomes, products, and agroecologies, an "Analytics" section presenting the effects of CSA practices through tables and visual graphics, and a "Resources" section offering relevant publications. The platform also hosts the Ethiopian Landscapes Restoration Platform (ELaRP), a collaborative effort involving 16 Ethiopian universities and the Alliance of Bioversity International and CIAT, which supports knowledge sharing and research on sustainable landscapes. The development of the CSA Knowledge Hub was made possible through the valuable contributions of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project and the Multifunctional Landscapes Research Program, whose support has been key in driving innovation and scaling CSA practices across Ethiopia.